2017
DOI: 10.1055/s-0037-1603744
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Properties of Brief Screening Tests for Alcohol Use Disorders during Pregnancy in Argentina

Abstract: Background Considering the physical, mental and behavioral problems related to fetal alcohol exposure, prenatal clinical guides suggest a brief evaluation of alcohol consumption during pregnancy to detect alcohol intake and to adjust interventions, if required. Even if any alcohol use should be considered risky during pregnancy, identifying women with alcohol use disorders is important because they could need a more specific intervention than simple advice to abstain. Most screening tests have been developed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
25
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 42 publications
0
25
0
3
Order By: Relevance
“…Alcohol use was measured using AUDIT-C [22, 23] derived from the 10-item alcohol use disorder identification test which is cross culturally validated and preferred tool to measure alcohol consumption [24, 25]. AUDIT-C has been used in different studies to measure alcohol use among pregnant women [9, 26, 27].…”
Section: Methodsmentioning
confidence: 99%
“…Alcohol use was measured using AUDIT-C [22, 23] derived from the 10-item alcohol use disorder identification test which is cross culturally validated and preferred tool to measure alcohol consumption [24, 25]. AUDIT-C has been used in different studies to measure alcohol use among pregnant women [9, 26, 27].…”
Section: Methodsmentioning
confidence: 99%
“…AUDIT-C has been demonstrated to perform with approximately equal accuracy to the full 10-item AUDIT and with superior accuracy compared to other alcohol self-assessment tools (Burns et al, 2010). It has been used in research to screen pregnant women for risky alcohol use and demonstrated high accuracy (Lopez et al, 2017;May, Hasken, et al, 2018). More in-depth measures (e.g., Timeline Follow-Back interview) were deemed inappropriate for this population due to high sensitivity related to alcohol use in the community, and a reluctance of participants to discuss alcohol use observed in previous studies.…”
Section: Methodsmentioning
confidence: 99%
“…The AUDIT has shown adequate psychometric properties in Argentine pregnant women (α = .93, Se = 87%, Sp = 86%) (López, Lichtenberger, Conde, & Cremonte, 2017). Risky consumption was considered when the BPR score was equal to or greater than eight, and when the APR score was equal to or greater than one (López et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…Possible dependence was considered when the BPR scores were equal to or greater than 16 (Babor et al, 1992), and when the APR scores were equal to or greater than four (López et al, 2017). (Table 3).…”
Section: Methodsmentioning
confidence: 99%